(untitled) (Orfeu, 2023)
This paper is dedicated to outlining and reflecting on andragogy strategies in the context of Higher Education from the musicality of oral tradition songs, in order to strengthen critical awareness. Based on discussions of the concepts of andragogy and critical thinking, especially in the view of Freire and Hooks, this work is constructed through reports of teaching actions, including the problematization of challenges that arise in approaching this content. Among its findings, the approach is shown to mobilize new learning through research, discussion and collective performance of songs whose lyrics, narratives, melodies, forms, rhythms and sociocultural context enrich training and promote the strengthening of critical thinking. It was also possible to verify the contributions of the proposals in the sphere of Education of Ethnic-Racial Relations, through research, critical analysis and dissemination of musical repertoires from different cultures. The problematization of musical repertoires in the processes of social transmission, memories, forgetting and silencing, are striking from the songs and their perpetuations or erasures.